2022
DOI: 10.3389/fphys.2022.941257
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of elevated VEGF in sepsis: A systematic review and meta-analysis

Abstract: Background: The incidence and mortality of sepsis are increasing year by year, and there is still a lack of specific biomarkers to predict its prognosis. Prognostic value of vascular endothelial growth factor (VEGF) in predicting the severity and mortality of sepsis has been gradually discovered.Methods: Literature was searched through Embase, PubMed, Web of Science, China National Knowledge Infrastructure(CNKI) and Cochrane Library databases in March 2022. Observational studies, evaluating the impact of VEGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…We found no signi cant differences in the serum VEGF levels between oliguric and non-oliguric patients. A systemic review and meta-analysis conducted by Tang, A. L. et al revealed that septic patients with high VEGF had poor clinical outcomes (13). However, signi cant heterogeneity between the reviewed studies challenges the study's conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no signi cant differences in the serum VEGF levels between oliguric and non-oliguric patients. A systemic review and meta-analysis conducted by Tang, A. L. et al revealed that septic patients with high VEGF had poor clinical outcomes (13). However, signi cant heterogeneity between the reviewed studies challenges the study's conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Serum vascular endothelial growth factor (VEGF) levels increase in early septic shock and contribute to increased vascular permeability (11). VEGF is also related to increased pulmonary vascular permeability and edema in sepsis-induced acute respiratory distress syndrome (ARDS) and is associated with poor clinical outcomes (12,13). However, the relationship between serum VEGF levels and tissue perfusion, oxygenation, and edema in sepsis is unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The results from a recent meta-analysis have demonstrated that VEGFA levels can also accurately predict sepsis mortality, with non-survivors presenting higher values [ 39 ]. Additionally, regarding LDHA, a number of studies have demonstrated that serum lactate levels could be of value in predicting mortality [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several observational studies exhibited a correlation of VEGF levels with sepsis prognosis, thus suggesting that VEGF could function as a potential biomarker for predicting disease severity and outcome [40][41][42][43]. A meta-analysis reinforced the predictive value of VEGF, thus indicating a strong correlation with a higher mortality risk in sepsis [44].…”
Section: Vegfmentioning
confidence: 99%